Wage Differentials in the Cotton Textile Industry, 1933-1952 - Mansfield, Edwin (The Review of Economics and Statistics, 1955)
DURING the past twenty years considerable work has been done concerning the behavior of wage differentials and wage dispersion.' In many of these studies attention has been confined to a particular wage differential, e.g., the North-South wage differential, and an attempt has been made to ascertain the average change over time in that differential in several industries. mere description of this important structural aspect of our industrial economy has general interest. Moreover, changes in wage dispersion and differentials imply shifts in the personal distribution of income which, in turn, have an impact upon the consumption function and upon resource allocation.2 It has been observed that in the period subsequent to the mid-I930's the personal distribution of income has become more nearly equal.3 This shift toward greater equality may be attributed, in part at least, to the absorption of the unemployed and the fuller employment of the partially employed. But changes in wage differentials can either strengthen or tend to offset the movement toward greater equality of income. Some studies have led to the conclusion that fuller employment accompanied by changes in wage differentials that strengthen the shift toward greater equality. Dunlop, Lebergott, and Ober,4 for example, have provided some empirical basis for the hypothesis that has been a trend toward a narrowing of the percentage differential between skilled and unskilled workers during the past half-century, and that the trend accentuated in boom periods of full employment and reversed in depressions. 5 This hypothesis has not gone unchallenged. Bell concludes that there is no logical pattern for cyclical variations in the structure of occupational differentials. . . . These cycli* This paper based largely on an M. A. thesis on file in the Duke University Library. work was done under the direction of Professor Frank A. Hanna and benefited from the comments of Professor Frank T. de Vyver. 1 See, for example, J. Dunlop, Cyclical Variations in Structure, this REVIEW, XXI (February 1939), 3039; S. Lebergott, Wage Structures, this REVIEW, XXIX (November I947), 274-85; H. Ober, 1907-1947, Monthly Labor Review, LXVII (August I948), I27-34; P. Bell, Cyclical Variation and Trend in Occupational Differentials in American Industry since 19I4, this REVIEW, XXXIII (November 1951), 329-37; J. Bloch, Regional Differentials; I907-46, Readings in Labor Economics, ed. F. Doody (Cambridge, Mass., 1950), 8I-9I; R. Lester, Differentials: Developments, Analysis, and Implications, Southern Economic Journal, XIII (April I947) 38694; H. Ober and C. Glasser, Regional Differentials, Monthly Labor Review, LXIII (October 1946), 5II-25; D. Roberts. The Meaning of Recent Changes, Insights into Labor Issues, ed. J. Shister and R. Lester (New York, 1948), 226-37; F. Meyers, Notes on Changes in the Distribution of Manufacturing Earners by StraightTime Hourly Earnings, 194I-48, this REVIEW, XXXII (November I950), 352-55; D. Brady, Equal Pay for Women Workers, Annals of the American Academy of Political and Social Science, XXLI (May 1947), 53-60. 2 It should be noted that the wage structure considered here the structure of average hourly earnings. Since the accounting period only one hour, this structure not strictly comparable with the personal distribution of income, in which the accounting period typically one year. In order to render them comparable, factors such as the variation among workers in annual hours of work must be taken into account. Despite the discrepancy, a direct relationship between the wage structure of an industry and the personal distribution of income would seem to exist. It should also be noted that the portion of labor income emanating from an industry in the form of salaries not included in the wage structure. Since average hourly earnings are used, the subsequent analysis concerned actually with the dispersion of average hourly earnings rather than the dispersion of wage rates. See J. Dunlop, op. cit., for a discussion of differences between average hourly earnings and wage rates. Attention here confined to the basic monetary remuneration of workers. In order to include the effects of fringe benefits in the analysis, data on the value per hour of such benefits to each worker would be required. Such data would provide new frequency distributions which would show the dispersion of average hourly earnings and fringe benefits combined. No such data are available. With regard to the North-South wage differential in the cotton textile industry, it has been suggested that fringe benefits tend to increase differences between the North and South. See the Report on the New England Textile Industry (by Committee Appointed by the Conference of New England Governors, 1952), pp. I37-43. 'H. Miller, Factors Related to Recent Changes in Income Distribution in the United States, this REVIEW, XXXIII (August 95I), 214-I8. 4 Dunlop, op. cit.; Lebergott, op. cit.; Ober, op. cit. 'Paraphrased in Bell, op. cit., p. 329.